Developing Islamic financial literacy in improving Islamic financial behavior towards the financial well-being of MSMEs: The moderating effect of e-payment usage - Rohmania, Aftuqa Sholikatur; Sholihah, Erlinda; Nurhapsari, Risma (Universitas Islam Indonesia, 2023)
IntroductionAs the country with the largest Muslim population in the world, Indonesia has the potential to develop the financial welfare of MSMEs as a driver of economic growth. However, studies on the financial well-being of MSMEs from an Islamic finance perspective are limited.ObjectivesThis study discusses the impact of Islamic financial literacy and Islamic financial behavior on the financial well-being of MSMEs, with e-payment usage as a moderating variable. MethodThis study used a quantitative approach with a sample of 200 culinary MSMEs in Semarang, Indonesia. Data collection was carried out using questionnaires, and data analysis was carried out using the partial least squares structural equation modelling technique.ResultsThe dimensions of Islamic financial literacy (Islamic financial knowledge, financial skills, and self-efficacy) have a significant positive effect on Islamic financial behavior. Islamic financial knowledge has no significant effect on financial well-being of MSMEs, whereas financial skills and self-efficacy have a significant positive effect. Islamic financial behavior has a significant positive effect on financial well-being of MSMEs. E-payment usage does not moderate the relationship between Islamic financial knowledge and financial skills towards Islamic financial behavior. ImplicationsThis study shows the importance of Islamic financial literacy and Islamic financial behavior to improving the financial welfare of MSMEs in Indonesia. The government and Islamic finance stakeholders in Indonesia need to continue to improve Islamic financial literacy and the Islamic financial behavior of society.Originality/NoveltyThis study contributes to the development of Islamic financial literacy and Islamic financial behavior as part of efforts to improve the financial welfare of MSMEs.